collaborative work in the teaching of statistics (Revista Electrónica REDINE, 2018)
The purpose of the research was to contextually argue the meanings that the actors assign to the teaching of statistics phenomenon. Given the complex, diverse and social ontology of the phenomenon, the episteme of the researchers is eminently qualitative, in whose phenomenological apprehension the phenomenological-hermeneutic method was used to interpret and understand the narrative of the social actors and the meaning-meaning that they give to the study phenomenon; for which the semi-structured in-depth interview was conducted. The epistemic reality of the study took place on the planes of the subjective and the intersubjective. The study's findings emerged from the students' experiential world through intersubjective consensus as a shared construction of knowledge. The interpretation of the findings was obtained from three (3) key informants that generated a theory of the teaching of applied statistics under the collaborative work approach.